2012
DOI: 10.1111/j.1747-0803.2012.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Induction by Transesophageal Electrophysiology Studies in Patients with Asymptomatic Ventricular Preexcitation

Abstract: TEEPS induced AFib in 88.5% of patients. Age, weight, height, and form of sedation had no effect upon AFib inducibility. TEEPS is an effective modality to induce AFib in pediatric patients with aVPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…TVEPS is an effective way to risk stratify patients; however, it is hampered by its invasiveness, cost, and potential complica-tions. TEEPS procedures have been shown to be an effective screening tool with potentially less complications; however no consensus anesthetic technique has been proven superior [2]. This study series describes our attempt to find the easiest, most effective anesthetic technique for the TEEPS procedure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…TVEPS is an effective way to risk stratify patients; however, it is hampered by its invasiveness, cost, and potential complica-tions. TEEPS procedures have been shown to be an effective screening tool with potentially less complications; however no consensus anesthetic technique has been proven superior [2]. This study series describes our attempt to find the easiest, most effective anesthetic technique for the TEEPS procedure.…”
Section: Discussionmentioning
confidence: 98%
“…TVEPS is currently accepted as the most effective way to assess the risk of these patients; however, this procedure is associated with increase cost, time, invasiveness, and risk. In contrast, a TEEPS is easy to perform, less costly, with less risk and excellent success rates [2].…”
Section: Introductionmentioning
confidence: 95%
“…However, the hospitalization cost, invasiveness, and risk of intracardiac electrophysiological examination are relatively increased. In contrast, TEEPS is easier to perform because of its lower cost, less risk, and higher success rate (Hoyt et al., 2013a). In this case, TEEPS showed that the QRS wave was still transmitted through the accessory pathway in S 1 S 2 500–220 ms, and the atrium entered the refractory period in S 1 S 2 500–210 ms.…”
Section: Figurementioning
confidence: 99%